Fourth-Order Runge-Kutta Method for Solving Applications of System of First-Order Ordinary Differential Equations - Aida, Mimi (Enhanced Knowledge in Sciences and Technology, 2022)
This paper illuminates the applicability and the efficiency of the fourth-order Runge-Kutta method (RK4), resulting in solving the application of system of first-order ordinary differential equations (ODEs). Two applications of system of first-order ODEs have been considered with initial condition which are arm race model and drug diffusion into human body model. The real-life application of these model has been discussed and applied in real-world. These applications have been solved by RK4 method by using different step size,  which are  and   with the help of MATLAB. The absolute error analysed are also carried out explicitly in the framework. At each point of interval, the value of the system has been calculated and compared with its exact value at that point. Moreover, for arm race model, a comparison of the computation is compared to existing method is worked out to illustrate the general advantage of proposed method.